PENGARUH MODEL INKUIRI BERBASIS PENDEKATAN STEAM TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD - Noval, Noval; tirsa, Aprima (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study investigates the effect of an inquiry-based learning model integrated with the STEAM approach on the IPAS learning outcomes of fifth-grade elementary students. The research was motivated by low student achievement due to teacher-centered instruction and limited student participation. A quantitative method with a pre-experimental one group pretest–posttest design was employed. The participants were 20 fifth-grade students of SDN 9 Tanjung Arak selected through saturated sampling. Data were collected using a validated and reliable learning outcomes test. Statistical analysis included normality testing, paired sample t-test, and N-Gain analysis. The findings revealed a significant improvement in student performance after the implementation of the inquiry-based STEAM model. The average score increased from 49.5 in the pretest to 69.75 in the posttest. The hypothesis test showed a significance value of 0.000 < 0.05, indicating a meaningful difference between pretest and posttest results. Thus, the model effectively enhances students’ learning outcomes and serves as an innovative instructional alternative.